2020
DOI: 10.1177/1055665620903186
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Mixed Longitudinal Study of Tooth Formation in Children With Clefts

Abstract: Objective: To test for systematic age changes in cleft children based on dental age. Design: Retrospective case–control longitudinal study. Setting: One orthodontic solo practice. Patients: Nonsyndromic, complete cleft lip and palateCLP cases, either unilateral or bilateral (102 children; 370 radiographs), between 4 and 16 years of age. Interventions: Children were treated with a team approach, but only orthodontic radiographs were studied. Main Outcome Measure: The principal outcome measure was dental age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Patients with UCLP had a significantly higher CA-DA difference than the controls; this was a key finding. The mean age of the UCLP subjects was underestimated by 0.319 years, thus indicating a possible delay in dental maturation; these results are consistent with previous research [21,22]. Van Dyck et al [23] systematically reviewed children with CL/P aged 5 to 13 years and noted that delayed dental development ranged from 0.2 to 0.9 years, with a mean delay of 0.56 years.…”
Section: Discussionsupporting
confidence: 83%
“…Patients with UCLP had a significantly higher CA-DA difference than the controls; this was a key finding. The mean age of the UCLP subjects was underestimated by 0.319 years, thus indicating a possible delay in dental maturation; these results are consistent with previous research [21,22]. Van Dyck et al [23] systematically reviewed children with CL/P aged 5 to 13 years and noted that delayed dental development ranged from 0.2 to 0.9 years, with a mean delay of 0.56 years.…”
Section: Discussionsupporting
confidence: 83%
“…Neither standard protocol for treatment nor the same local influences were present in the study group. Results of previous studies showed disparity in dental development of patients with and without clefts, and no pattern in dental development in children with CL/P was universally noticed (Pöyry et al, 1989; Tan et al, 2012; Almotairy & Pegelow, 2018; Kimbrough et al, 2020). Diversity of influences in study group, along with the fact that no pattern in dental development was established so far, was taken into account when study sample in the present study was created.…”
Section: Discussionmentioning
confidence: 80%